Global Initiative on AI for Health (GI-AI4H): strategic priorities advancing governance across the United Nations - Vijaytha Muralidharan; Madelena Y. Ng; Shada AlSalamah; Sameer Pujari; Kanika Kalra; Rajeshwari Singh; Denise Schalet; Tobi Olantuji; Rohit Malpani; Rubeta N. Matin; Jesutofunmi A. Omiye; Yu Zhao; et al. (npj Digital Medicine)
Abstract The Global Initiative on Artificial Intelligence for Health (GI-AI4H), established by the World Health Organization, serves to harmonize governance standards for artificial intelligence (AI). The GI-AI4H spearheads novel on-the-ground efforts, especially in low- and middle-income countries, to advance ethical, regulatory, implementation, and operational dimensions of global governance for health AI. The GI-AI4H’s efforts across the United Nations drives safe, ethical, equitable, and sustainable health AI use for the global community.